Aplikasi DMAIC Dalam Metode Six Sigma dan Eksperimen Shainin Bhote Sebagai Penurunan Persentase Cacat - Kholik, Heri M. (Jurnal Teknik Industri, 2008)
PT. Bumi Buana Citra Malang found the existence of problems that is, company find difficulties in degrading the amount of defect product. This matter [is] caused [by] the existence of variation in determining usage of configuration of level at process parameter, like happened variation determination of temperature of furnace, temperature of molten metal, determination of molding time and determination of pressurizing sand. Existence of variation in determination level configuration of the process parameter result incidence of defect product which height affect of expense defect product which must be accounted by company. To overcome the problem, Six-Sigma method was selected. Six Sigma is a logical procedure by following cycle of DMAIC to execute to repair of process by [doing/conducting] improvement and operation of quality result of production. In cycle of DMAIC early by determining the target of and accurate object, conducting measurement to ability of process at company, conducting observation to cause factors incidence problems by using experiment method of Shainin Bhote as supporter method, executing planning of repair according to from result of [at] previous phase and terminated by documenting repair pickings which have successful executed by using process operation of statistic. From applying of method of Six Sigma, company can degrade the amount of defect product which initially 129 unit of per-months become 25 units during period of repair or experience of degradation equal to 80, 6%. To the expense of effect of defect product which initially equal to Rp.12.996.750,00 per-months become equal to Rp.2.518.750,00 or happened thrift equal to 80,6% during period of repair. Beside that by using system of DMAIC in method of Six Sigma will be obtained a determination of configuration of level [at] better process and can improve level of operation of company.